2020
DOI: 10.1007/s10484-020-09484-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Illusory Choice Used as a Variant of Situation Selection for Regulating Emotions: Reduction of Positive Experience But Preservation of Physiological Downregulation

Abstract: Situation selection is an emotion regulation strategy consisting in choosing a future emotional situation. Past research showed that Situation selection triggers a decrease in negative experience, exocrine reactions and respiratory activity, while maintaining stable positive experience. In this study, we wanted to replicate these observations and test emotional responses that follow an Illusory choice, i.e., when the chosen situation is not available and replaced by another. Sixty-eight participants watched em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Several studies tested if sense of agency influences participants' self-reported emotional states. Most experiments found that having a degree of choice over one's actions and/or a feeling of control over ensuing action effects led to more positive or less negative affect (Abelson et al, 2008 ; Thuillard and Dan-Glauser, 2017 , 2020 ; Stolz et al, 2020 ; Li et al, 2021 ). Moreover, participants prefer tasks which allow them to make choices compared to tasks where they cannot choose between different options, even when their own choices are not more likely to result in better outcomes (Leotti and Delgado, 2011 , 2014 ; Fujiwara et al, 2013 ; Cockburn et al, 2014 ; Mistry and Liljeholm, 2016 ; Bobadilla-Suarez et al, 2017 ; Wang and Delgado, 2019 ).…”
Section: Does Sense Of Agency Influence Affective Processing?mentioning
confidence: 99%
“…Several studies tested if sense of agency influences participants' self-reported emotional states. Most experiments found that having a degree of choice over one's actions and/or a feeling of control over ensuing action effects led to more positive or less negative affect (Abelson et al, 2008 ; Thuillard and Dan-Glauser, 2017 , 2020 ; Stolz et al, 2020 ; Li et al, 2021 ). Moreover, participants prefer tasks which allow them to make choices compared to tasks where they cannot choose between different options, even when their own choices are not more likely to result in better outcomes (Leotti and Delgado, 2011 , 2014 ; Fujiwara et al, 2013 ; Cockburn et al, 2014 ; Mistry and Liljeholm, 2016 ; Bobadilla-Suarez et al, 2017 ; Wang and Delgado, 2019 ).…”
Section: Does Sense Of Agency Influence Affective Processing?mentioning
confidence: 99%